The Effects of Corona Virus Pandemic on Children - Tumwesigye, Keneth (Salasika, 2021)
Abstract Background. With the outbreak of the deadly COVID -19 worldwide, children are at the risk of child abuse due to rising unemployment rates and school closures. The corona virus pandemic has caused a lot of stress especially to parents and guardians who have lost their jobs and such stress has heightened and increased family violence especially abuse against children. Methods A sample of 26 Child welfare professionals (64% female and 36% male ) practicing in Uganda completed a web survey regarding the COVID-19 experiences especially in connection to child welfare service delivery and well being during the COVID-19 pandemic. Results This study identified the impact of corona virus pandemic on the life of children associated with child abuse and their coping measures. The fact that COVID-19 will continue to spread rapidly worldwide has caused immense consequences in regard to children’s safety and well-being. The major consequence of the pandemic is the risk of increased child maltreatment perpetuated by parents who lost their jobs as a result of the pandemic. This study identified parental job loss during the COVID-19 pandemic as the main cause for child maltreatment and physical abuse. Nevertheless, the findings support cognitive reframing as a measure to control physical abuse by parents. The financial hardships caused by COVID-19 pandemic will continue to negatively impact children’s safety and well-being. The consequences of COVID-19 pandemic are evident that the risk of child maltreatment increases as stress accumulates. Conclusion In conclusion, as world leaders and scientists make efforts to tackle the public health and economic threat resulting from the COVID-19 pandemic; further research on the impact of COVID-19 on family existence and functioning will be significant in establishing empirically based policies, interventions and different practices to support victims of child maltreatment and physical abuse.